2007
DOI: 10.1177/0748730407303387
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppression and Circadian Function

Abstract: Circadian clock and cell division cycle are two fundamental biological processes. The circadian clock is the body's molecular time-keeping system, while the cell division cycle regulates development and cellular renewal. The expression of cell cycle genes such as Wee1, Cyclins, and c-Myc are under circadian control and could be directly under the regulation of the circadian transcriptional complex. This complex is composed of heterodimer transactivators CLOCK/NPAS2 with BMAL1, which regulate the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 70 publications
(84 reference statements)
2
87
0
Order By: Relevance
“…A proto-oncogene protein c-MYC regulates the G 0 to G 1 transition of the cell cycle, and c-Myc has shown to be under circadian regulation in mice (Lee, 2006). Accumulating evidence in mammals reveals that some essential checkpoint elements in the cell cycle, including c-Myc (G 0 /G 1 transition), Cyclin D1 (G 1 /S transition), and WEE1 (G 2 /M transition) are under circadian control (Chen-Goodspeed and Lee, 2007;Hunt and Sassone-Corsi, 2007;Sahar and Sassone-Corsi, 2009). Overall, peripheral circadian clock-mediated tran--lar proliferation and major tissue activities for optimizing local rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…A proto-oncogene protein c-MYC regulates the G 0 to G 1 transition of the cell cycle, and c-Myc has shown to be under circadian regulation in mice (Lee, 2006). Accumulating evidence in mammals reveals that some essential checkpoint elements in the cell cycle, including c-Myc (G 0 /G 1 transition), Cyclin D1 (G 1 /S transition), and WEE1 (G 2 /M transition) are under circadian control (Chen-Goodspeed and Lee, 2007;Hunt and Sassone-Corsi, 2007;Sahar and Sassone-Corsi, 2009). Overall, peripheral circadian clock-mediated tran--lar proliferation and major tissue activities for optimizing local rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of cell death result from P53-dependent apoptosis, a process that involves several rhythmic components (Granda et al 2005;Gery et al 2006). Furthermore, both P53 expression and apoptosis were downregulated by circadian disruption through Per2 mutation, Per1 knockout cells or chronic jet lag Gery et al 2006;Chen-Goodspeed & Lee 2007). Thus, the molecular interactions between the circadian clock and the cell cycle and its related apoptosis pathways represent a major determinant of 5-FU chronotolerance (figure 2).…”
Section: Experimental Chronotherapeutics With 5-fluorouracil and Oxalmentioning
confidence: 99%
“…NPAS2:BMAL1 protein dimers, in particular, play a key role in the molecular clock through the activation of the transcription of the clock genes Per and Cry (Lévi & Schibler 2007;Liu et al 2007). This protein dimer also exerts a negative control on the cell cycle, both through the repression of c-myc and p21, two important players in cellular proliferation and apoptosis, and through the activation of p53, a pro-apoptotic gene, and wee1, whose protein gates cell cycle transition from G2 to mitosis (Matsuo et al 2003;Chen-Goodspeed & Lee 2007;Okyar & Lévi 2008). In proliferating cells, this results in the circadian control of the transition from G1 to S and from G2 to M (Matsuo et al 2003;Lévi et al 2007a).…”
Section: Mechanisms Of Circadian Rhythms and Therapeutic Implicationsmentioning
confidence: 99%
“…Seliciclib was most efficient when administered at a time corresponding to the time at which treatment established the proper phase relationship of the oscillating clock genes (13). Several experiments employing cell lines have demonstrated that increased per gene expression leads to the suppression of growth of the transformed cells (17)(18)(19), and per2 has been suggested as a novel therapeutic strategy for the treatment of malignant tumors (20,33).…”
Section: Discussionmentioning
confidence: 99%